Kepemimpinan Kontingensi Sebagai Upaya Kepala Sekolah Untuk Meningkatkan Kinerja Guru (Studi Kasus di SDIT An Naajiyah Kubu Raya) - Arifianto, Anggistia Ninda; Suwito Eko Pramono; Agung Kuswantoro; Banna Irfan Ibadillah; Alin Safaraz Himam (Rayah Al-Islam, 2026)
This study was motivated by the urgent need for adaptive leadership in integrated Islamic schools to respond to the fluctuating dynamics of teacher performance. The main focus of this study is to analyze the implementation of contingent leadership by the principal in carrying out his functions as a leader, motivator, and educator at SDIT An Naajiyah Kubu Raya. Using a descriptive qualitative approach through a case study design, data were collected through non-participatory observation techniques, semi-structured interviews with the principal and five teachers, as well as curriculum and management documentation. Data analysis was conducted interactively, including data reduction, data presentation, and conclusion drawing. The results of the study show that the principal functions as a leader who demonstrates the ability to adapt his leadership style to various situations that occur at school. The principal functions as a motivator through the creation of a positive work climate, the giving of rewards, and moral and spiritual support. The principal functions as an educator through the implementation of academic supervision, professional development, and ongoing mentoring. Overall, the principal is able to comprehensively carry out his role as a leader, motivator, and educator in improving the quality of performance and the learning environment at school. The novelty of this study lies in the integration of Fiedler's contingency theory with Islamic leadership values in the context of elementary schools. The implication is that this model has proven effective in creating a conducive work climate and significantly improving teacher professionalism amid the challenges of 21st-century education.